Mark Manders : Ornament met brandpunten. (Amsterdam : Roma Publications Amsterdam, 2000)
Poems by Manders. The abstract cover fits as well to the title as to the precize but distant descriptions that create an penetrative mental perception of a fictive person.
Nederlands
boek
Keywords: Manders, Mark